Bringing Bach's music to life essays on Bach cantatas - Smith, Craig 1947-2007 (Pendragon Press, 2019)
With a unique relationship to Bach's works and their liturgical function, Craig Smith engages the cantatas as living works of art, exploring how they work musically, emotionally, and theologically. Integrating spiritual, psychological, and compositional analysis, these vivid essays reveal Bach's power to communicate complex messages of faith, doubt, and the human condition. In the Foreword, eminent composer and close friend of Smith, John Harbison, writes: "Craig's writing embraces, at times dissolves, never ignores, the distance - esoteric, temporal, linguistic, cultural - that the Bach cantatas carry. The paternalistic theology, the presentness of sin, the Devil, the rough proximity of Death is never evaded or finessed. That which should remain difficult is acknowledged. That which immediately attracts is gratefully received. What is constantly suggested is that this may be the finest music that the finest composer wrote, and that it is never too late to catch up to it."
Keywords: Bach, Johann Sebastian -- 1685-1750 -- Kantaten; Bach, Johann Sebastian / 1685-1750 / Cantatas; Cantatas / History and criticism; Cantatas (Bach, Johann Sebastian); Cantatas; Criticism, interpretation, etc